The analysis of MF resin and CaCO3 diffuser-loaded encapsulations to enhance the homogeneity of correlated color temperature for phosphor-converted LEDs - My Hanh Nguyen Thi; Phung Ton That (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2021)
The most popular method used in the production of phosphor-converted LEDs (pc-LEDs) is dispensing phosphor freely. However, this method is inferior in generating good angular correlated color temperature (CCT) homogeneity. Thus, in this article, a diffuser-loaded encapsulation is proposed as a potential solution for better CCT uniformity. The paper provides a detailed investigation on how melamine formaldehyde (MF) resin and CaCO3 loaded encapsulations impact the uniformity of CCT, as well as the lumen efficacy of pc-LEDs. The results demonstrate that between MF resin and CaCO3 loaded encapsulations, the MF resin yields a higher light diffusion efficiency while the CaCO3 maintains greater lumen efficacy. The photon scattering development is the key force behind the enhancement of the angular CCT uniformity in pc-LEDs’ output when using the loaded encapsulations of MF resin and CaCO3 particles. Since this package utilized mineral, it has reasonable cost and is quite easy to control while still being effective in enhancing the angular CCT homogeneity of pc-LEDs. Diffusers with 1% concentration of MF resin or 10% concentration of CaCO3 are determined as an optimal solution for reducing the variance of angular CCT and increasing the lumen output.